2007
DOI: 10.1007/s00464-006-9186-4
|View full text |Cite
|
Sign up to set email alerts
|

PROSPECT: a practical method for formulating evidence-based expert recommendations for the management of postoperative pain

Abstract: Transparency in PROSPECT processes allows the users to be fully aware of any limitations of the evidence and recommendations, thereby allowing for appropriate decisions in their own practice setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 36 publications
0
43
0
5
Order By: Relevance
“…Such a program permitted a more rapid postoperative return of normal cardiopulmonary response to treadmill exercise and facilitated return of overall exercise capacity 6 weeks after surgery (Basse It can be seen from the foregoing that a multi-interventional and rehabilitation strategy is required, including very effective pain relief, if optimal outcomes are to be achieved, as outlined in procedure-specific recommendations from the PROSPECT group (Kehlet et al, 2007). Postoperative rehabilitation should include pharmacological, physical, psychological and nutritional components (Figure 1.4).…”
Section: Pain and Analgesia: Effects On Injury-induced Organ Dysfunctionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such a program permitted a more rapid postoperative return of normal cardiopulmonary response to treadmill exercise and facilitated return of overall exercise capacity 6 weeks after surgery (Basse It can be seen from the foregoing that a multi-interventional and rehabilitation strategy is required, including very effective pain relief, if optimal outcomes are to be achieved, as outlined in procedure-specific recommendations from the PROSPECT group (Kehlet et al, 2007). Postoperative rehabilitation should include pharmacological, physical, psychological and nutritional components (Figure 1.4).…”
Section: Pain and Analgesia: Effects On Injury-induced Organ Dysfunctionmentioning
confidence: 99%
“…Several randomised controlled studies have shown that the addition of glucocorticoids reduces postoperative pain and analgesic requirement (see below). Additional benefits include decreased PONV and fatigue (Romundstad et al, 2006;Kehlet, 2007).…”
Section: Glucocorticoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Maternal satisfaction from this protocol and the use of rectal analgesia has not been previously studied. Also, the use of opioids is associated with side effects such as nausea, vomiting, confusion, constipation, tolerance and physical dependency 9,10,11 .…”
Section: Introductionmentioning
confidence: 99%